Effect of glycaemic control on cardiovascular disease in individuals with type 2 diabetes with pre‐existing cardiovascular disease: A systematic review and meta‐analysis. Issue 3 (18th December 2018) - Barer, Yael; Cohen, Ohad; Cukierman‐Yaffe, Tali
Abstract : The role of intensive glucose control in people with type 2 diabetes and pre‐existing cardiovascular disease (CVD) is controversial. The aim of this systematic review and meta‐analysis was to determine in a subset of people with type 2 diabetes and pre‐existing CVD, the CV effect of intensive glucose control versus standard of care. We searched Medline, the Cochrane library, EMBASE and the National Institutes of Health Trial registration database for randomized controlled trials that evaluated the effect of intensive glucose control versus standard glucose control in people with type 2 diabetes on incident CVD. Data were extracted using a structured form. When data were not available in the publications, authors were contacted. Eight trials involving 8339 participants were included. Among adults with type 2 diabetes and pre‐existing CVD, there was no difference in the risk of CV events in those allocated to intensive glucose control compared with those in the standard care arm (relative risk 0.98, 95% confidence interval 0.87‐1.09). In conclusion, in people with diabetes and pre‐existing CVD, intensive glucose control versus standard care had a neutral effect on incident CV events.